1899 S.D. Stat. 972, ch. 107, Political Code, § 3240 (Vol. 1) - (:unkn) unknown (General Publisher, 1899)
Prohibited [a]t any time kill[ing] or shoot[ing] any wild duck, goose or brant with any swivel gun or other gun, except as is commonly shot form the shoulder, or in hunting such birds makes us of any artificial light or battery. . .
--
Keywords: HUNTING REGULATION